2021
DOI: 10.1002/chem.202004630
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion–Protein Interactions Influence Bacterial Ice Nucleation

Abstract: Ice nucleation‐active bacteria are the most efficient ice nucleators known, enabling the crystallization of water at temperatures close to 0 °C, thereby overcoming the kinetically hindered phase transition process at these conditions. Using highly specialized ice‐nucleating proteins (INPs), they can cause frost damage to plants and influence the formation of clouds and precipitation in the atmosphere. In nature, the bacteria are usually found in aqueous environments containing ions. The impact of ions on bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Copyright 2020 American Chemical Society. (D) Freezing spectra of P. syringae in pure water and in the presence of 0.5 mol/kg MgSO 4 (purple), NaSCN (blue), NH 4 Cl (red) in water and of NaSCN (light blue), NH 4 Cl (light red) in PBS buffer adapted with permission from ref ( 46 ). Copyright 2021 Wiley-VCH.…”
Section: Resultsmentioning
confidence: 99%
“…Copyright 2020 American Chemical Society. (D) Freezing spectra of P. syringae in pure water and in the presence of 0.5 mol/kg MgSO 4 (purple), NaSCN (blue), NH 4 Cl (red) in water and of NaSCN (light blue), NH 4 Cl (light red) in PBS buffer adapted with permission from ref ( 46 ). Copyright 2021 Wiley-VCH.…”
Section: Resultsmentioning
confidence: 99%
“…Govindarajan et al further showed that delipidating membranes abolished the activity of class C INs and that the addition of lipids reconstituted activity . A number of studies also revealed that chemicals that disrupt the fluidity of the membrane reduced ice nucleation activity. ,, Recent studies further showed that environmental factors (pH, salts, antifreeze proteins) can have very different effects on class A and class C INs. , Here, we use the high-throughput twin-plate ice nucleation assay (TINA) to investigate the ice nucleation activity of the lipids 1,2-dimyristoyl-3-trimethylammonium −propane (DPTAP), 1,2-dipalmitoyl- sn -glycero-3-phosphoglycerol (sodium counterion) (DPPG), 1,2-dipalmitoyl- sn -glycero-3-phosphorylethanolamine (chloride counterion) (DPPE), phosphatidylinositol (PI), lipopolysaccharides, and the effects of deuterated water, heat, and delipidation on the ice nucleation activity of P. syringae …”
mentioning
confidence: 99%
“…Our data is consistent with a mechanism, in which bacteria have to exert precise control over (1) the distance between the INP monomers at the sub-Ångstrom level, and (2) the size of the protein assemblies to achieve high ice nucleation activities. 10 This mechanism explains the high sensitivity of class A INs to temperature as well as chemicals 7,11,17,19 that modify the properties of the cell membrane or the aggregation behavior of proteins. Given that highly active class A INs have also been observed in mutated E. coli cells 12 suggests that INP assembly is robust toward variations in exact membrane composition.…”
mentioning
confidence: 99%
“…Fusarium acuminatum (F. acuminatum) and Fusarium avenaceum (F. avenaceum) have been identified in the atmosphere and have been found to be effective INSs in the immersion mode (Amato et al, 2007;Hasegawa et al, 1994;Pouleur et al, 1992;Richard et al, 1996;Seifi et al, 2014). Cultures were obtained from the American Type Culture Collection (ATCC catalog numbers 60315 and 200466 for F. acuminatum and F. avenaceum, respectively) and grown in potato dextrose broth for 3-4 d at approximately 21 • C shaking at 50 rpm.…”
Section: Fungimentioning
confidence: 99%